Understanding gas-enhanced methane recovery in graphene nanoslits via molecular simulations - Dias Bekeshov; Sultan Ashimov; Yanwei Wang; Lei Wang (Capillarity, 2023)
Shale gas and coalbed methane are energy sources that mainly consist of methane stored in an adsorbed state in the pores of the organic-rich rock and coal seams. In this study, the graphene nanoslit model is employed to model the nanometer slit pores in shale and coal. Grand canonical Monte Carlo and molecular dynamics modeling methods are used to investigate the mechanisms of adsorption and displacement of methane in graphene-based nanoslit pores. It is found that as the width of the slit pore increases, the adsorption amount of gas molecules increases, and the number density profile of adsorbed methane molecules alters from monolayer to multilayer adsorption. The minimum slit pore width at which methane molecules can penetrate the slit pore is determined to be 0.7 nm. Moreover, it is demonstrated that by lowering the temperature, the adsorption rate of the methane increases since the adsorption is an exothermic process. Enhancing methane recovery was investigated by the injection of gases such as CO2 and N2 to displace the adsorbed methane. The comparison of adsorption isotherms of gas molecules provides the following order in terms of the amount of adsorption, CO2 > CH4 > N2, for the same slit pore width and the same temperature and pressure conditions. Document Type: Original article Cited as: Bekeshov, D., Ashimov, S., Wang, Y., Wang, L. Understanding gas-enhanced methane recovery in graphene nanoslits via molecular simulations. Capillarity, 2023, 6(1): 1-12. https://doi.org/10.46690/capi.2023.01.01